2015
DOI: 10.1007/s11906-015-0549-x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Energy Balance by the Brain Renin-Angiotensin System

Abstract: The renin-angiotensin system (RAS) exists as a circulating hormone system but it is also used by various tissues of the body, including the brain, as a paracrine signaling mechanism. The local brain version of the RAS is mechanistically involved in fluid balance and blood pressure control, and there is growing appreciation for a role of the brain RAS in the control of energy balance. Here, we review major evidence for the control of energy balance by the brain RAS; outline the current understanding of the RAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 89 publications
1
20
0
2
Order By: Relevance
“…Not only does adipose tissue have a local RAS 12,28 but serum levels of major the components of the RAS (renin, AGT, ACE) are elevated in obesity. 10 TNF-α is commonly considered as one of the initiators of the pro-inflammatory cascade, which can induce the production of other cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does adipose tissue have a local RAS 12,28 but serum levels of major the components of the RAS (renin, AGT, ACE) are elevated in obesity. 10 TNF-α is commonly considered as one of the initiators of the pro-inflammatory cascade, which can induce the production of other cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin action at proopiomelanocortin (POMC) neurons of the ARC is critical for BP regulation (8), and both POMC and agouti-related peptide (AgRP) neurons mediate the metabolic effects of leptin in the ARC. While the brain RAS has been implicated in the control of selected aspects of energy balance including food intake and energy expenditure, the specific brain regions involved and the neurocircuitry that mediates these effects are unknown (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that obesity causes chronic low-grade inflammation associated with systemic metabolic dysfunction that is accompanied by increased renin-angiotensin system (RAS) activity. 1,2 Recent studies have demonstrated that the RAS and proinflammatory cytokines (PICs) in the central nervous system (CNS) play a critical role in mediating obesity-induced sensitization and obesity-related hypertension. 3,4,5 …”
Section: Introductionmentioning
confidence: 99%